The Smallest Spectral Radius of Graphs with a Given Clique Number - Jing-Ming Zhang; Ting-Zhu Huang; Ji-Ming Guo (The Scientific World Journal)
The first four smallest values of the spectral radius among all connected graphs with maximum clique size ω≥2 are obtained.